2-D analytical model for dual-stator machines with permanent magnets - Golovanov, Dmitry; Galea, Michael; Gerada, C. (2016)
This paper proposes an analytical model that considers the torque characteristics and results in an optimum geometry for dual-stator synchronous machines with permanent magnets. The distribution of the magnetic field in the air gap is obtained by solving Neumann’s problem by using Green’s function. The results of the study shows that the dual-stator topology of synchronous machine with permanent magnets can achieve up to 1.7 times more torque when compared to conventional machine with radially magnetized magnets. This effect is achieved due to more efficient using of the volume of the machine. The analytical model presented in the paper allows fast but accurate optimization of the machine’s geometry and is used to achieve an optimal design for the considered application.